PENGARUH KAP SPESIALIS INDUSTRI, KAP BIG FOUR DAN MASA PERIKATAN AUDITOR TERHADAP MANAJEMEN LABA DENGAN EFEKTIVITAS KOMITE AUDIT SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN NON-KEUANGAN DI BURSA EFEK INDONESIA TAHUN 2016 - Fathoni, Rialdi Fuad (Diponegoro Journal of Accounting, 2020)
This study aims to analyze the effect of audit quality on earnings management with the effectiveness of the audit committee as a moderating variable. Proxies used for audit quality in this study are industry specialist auditors, KAP big four, and auditor engagement period. This study uses a total sample of 183 non-financial companies listed on the Indonesia Stock Exchange in 2016. The data used in this study are secondary data containing data regarding the date of publication of the company's financial statements on the IDX website and annual reports of companies listed on the IDX 2016. The procedure for selecting samples uses the purposive sampling method and uses multiple linear regression analysis as a data analysis technique in this study. Statistical test results show that the big four KAP which is moderated by the effectiveness of the audit committee has a negative effect with a coefficient value - 0.00 and significant with a probability value of 0.04 on earnings management. However, industry specialist auditors that are moderated by the effectiveness of the committee have a positive effect with a coefficient of -0.00 and are not significant with a probability value of 0.98 and the engagement period of the auditor moderated by the effectiveness of the audit committee has a negative effect with a coefficient of -0.00 and is insignificant with a probability value of 0,29 towards earnings management.